2021
DOI: 10.1038/s41419-021-03991-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-301a-3p induced by endoplasmic reticulum stress mediates the occurrence and transmission of trastuzumab resistance in HER2-positive gastric cancer

Abstract: Trastuzumab resistance negatively influences the clinical efficacy of the therapy for human epidermal growth factor receptor 2 (HER2) positive gastric cancer (GC), and the underlying mechanisms remain elusive. Exploring the mechanisms and finding effective approaches to address trastuzumab resistance are of great necessity. Here, we confirmed that endoplasmic reticulum (ER) stress-induced trastuzumab resistance by up-regulating miR-301a-3p in HER2-positive GC cells. Moreover, we elucidated that miR-301a-3p med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…miR-301a-3p, belonging to the mir-130/301 family, is a multifunctional miRNA that promotes tumor progression, regulates inflammatory responses, and mediates drug resistance [ 28 30 ]. miR-301a-3p can promote tumor proliferation and metastasis in several malignancies, including esophageal, pancreatic, and colorectal cancer [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-301a-3p, belonging to the mir-130/301 family, is a multifunctional miRNA that promotes tumor progression, regulates inflammatory responses, and mediates drug resistance [ 28 30 ]. miR-301a-3p can promote tumor proliferation and metastasis in several malignancies, including esophageal, pancreatic, and colorectal cancer [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms whereby FGFR prevents trastuzumab binding have not yet been determined, recent studies have unveiled the relevant role of micro-RNAs in gastric cancer HER2-positive cells. Guo et al proposed that miR-301a-3p disseminated TZ resistance by activating the expression of FGFR1 through the intercellular transfer of this micro-RNA by exosomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…In response to HER2 targeting, other receptors can compensate for HER2 loss by maintaining activation of shared downstream pathways. Ten studies demonstrated MET receptor upregulation following inhibition of the HER2 receptor in resistant models [46][47][48][49][50][51][52][53][54][55], whilst others described the contributions of other ErbB receptor family members (n = 7) [28,37,46,[56][57][58][59], fibroblast growth factor receptors (FGFR) (n = 4) [34,[60][61][62], or other receptors (n = 6) [36,52,61,[63][64][65].…”
Section: Alternative Receptor Signalingmentioning
confidence: 99%